2024
DOI: 10.1051/0004-6361/202348427
|View full text |Cite
|
Sign up to set email alerts
|

JWST Observations of Young protoStars (JOYS+): Detecting icy complex organic molecules and ions

W. R. M. Rocha,
E. F. van Dishoeck,
M. E. Ressler
et al.

Abstract: Complex organic molecules (COMs) are ubiquitously detected in the gas phase and thought to be mostly formed on icy grains. Nevertheless, there have not been any unambiguous detections of COMs larger than CH$_3$OH in ices reported thus far. Exploring this matter in greater detail has now become possible with the unprecedented possibilities offered by the James Webb Space Telescope (JWST) within the infrared (IR) spectral range with its very high sensitivity and spectral resolution in the critical 5$-$10 mu m ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 158 publications
2
9
0
Order By: Relevance
“…These studies have shown that the SO 2 in these high-mass systems resides at typical temperatures of ∼100−300 K, although higher temperatures of up to 700 K have also been reported (Keane et al 2001). The average abundances with respect to H 2 are >10 −7 , which is consistent with the SO 2 abundance of interstellar ices (Boogert et al 1997(Boogert et al , 2015Zasowski et al 2009;McClure et al 2023;Rocha et al 2024) and cometary ices (Altwegg et al 2019;Rubin et al 2019), suggesting that gaseous SO 2 may originate from ice sublimation in the inner hot cores of these high-mass protostellar systems. A MIR detection of gaseous SO 2 , either in absorption or emission, toward low-mass protostellar systems is, to the best of our knowledge, still lacking.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…These studies have shown that the SO 2 in these high-mass systems resides at typical temperatures of ∼100−300 K, although higher temperatures of up to 700 K have also been reported (Keane et al 2001). The average abundances with respect to H 2 are >10 −7 , which is consistent with the SO 2 abundance of interstellar ices (Boogert et al 1997(Boogert et al , 2015Zasowski et al 2009;McClure et al 2023;Rocha et al 2024) and cometary ices (Altwegg et al 2019;Rubin et al 2019), suggesting that gaseous SO 2 may originate from ice sublimation in the inner hot cores of these high-mass protostellar systems. A MIR detection of gaseous SO 2 , either in absorption or emission, toward low-mass protostellar systems is, to the best of our knowledge, still lacking.…”
Section: Introductionsupporting
confidence: 52%
“…In order to fit the SO 2 emission in the ν 3 band, the local continuum had to be subtracted. However, the spectral region surrounding the emission features is dominated by absorption of ices such as the 7.25 and 7.4 µm ice bands that are typically ascribed to complex organics including ethanol (CH 3 CH 2 OH) and acetaldehyde (CH 3 CHO) or the formate ion (HCOO − ; e.g., Schutte et al 1999;Öberg et al 2011;Boogert et al 2015;Terwisscha van Scheltinga et al 2018;Rocha et al 2024). A fourth-order polynomial was fitted through obvious linefree channels (i.e., 7.015, 7.113, 7.162, 7.442, 7.489, 7.545, and 7.635 µm; see the top panel of Fig.…”
Section: Alma Datamentioning
confidence: 99%
See 3 more Smart Citations